Penyuluhan Fisioterapi Mengenai Low Back Pain Pada Relawan SAR Kota Surakarta - Aulia Marsha Panandita; Khonsa Qonita Ramadhani; Devi Rahma Fadila (Pusat Riset dan Inovasi Nasional, 2022)
Low Back Pain (LBP) is one of the most popular health problem in society. The World Health Organization (WHO) states that there are 150 types of musculoskeletal disorders experienced by millions of people causing pain, inflammation, and functional limitation that will affect psychology and quality of life. Therefore, it is necessary to take steps for control the incidence of LBP and prevent complication due to LBP that can implemented to the community. This activity aims to increase the understanding of community members about Low Back Pain. Community service activities carried out in the form of physiotherapy counseling orderly with talkative method using power point and leaflets. Based on the response of the participants amount 8 respondents, it was found that before the delivered of material there were 3 people (37,5%) who had fair level of knowledge and 5 people (62.5%) had good level of knowledge about LBP. Meanwhile, after the counseling process, there were 8 people (100%) had a good level of knowledge about LBP. In conclusion, education and counseling had a good impact for increasing the knowledge of community members about Low Back Pain.